Life Cycle Analysis of Sotol Production in Mexico - Madrid Solórzano, Juan Manuel (2021)
Sotol is a Mexican distilled spirit produced in Northern Mexico. The estimated annual production of sotol is at around 5,200 hl per year. This industry grows at an average rate of 5% per year. The Mexican Sotol Council and the Sotol Certificate Council are regulatory bodies dedicated to monitoring that sotol producers comply with the Official Mexican Standard NOM-159-SCFI-2004. Currently, those regulatory bodies try to improve the sotol production process and good practice guidelines to contribute to cleaner production. This paper reports a case study of artisanal sotol production in Chihuahua State in Mexico. Life cycle assessment (LCA) technique was used to compute the environmental impact of sotol and its performance to identify system hotspots and propose improvement interventions. SimaPro software, v.9.1®, is used for the LCA, applying CML-IA baseline V3.05/EU25 method to evaluate and select environmental impact categories. The system boundary included the stages of harvest, cooking, milling, fermentation, distillation, bottling, and packaging. The findings indicate that each of the stages required for sotol beverage processing significantly affects the marine ecosystem. The milling and bottling stages have the highest environmental impact. A 750-ml bottle of artisan sotol causes 5.92 kg CO2 eq, based on empirical data. Sotol makers should focus on reducing energy consumption caused by input transportation and equipment for milling.